Pengembangan Instrumen Penilaian Sikap Praktikum Fisika Dasar I Pada Mahasiswa Jurusan Pendidikan Fisika Uin Alauddin Makassar - Anas Irwan; Muhammad Arsyad; Kaharudin Arafah (Department of Physics Education, Universitas Mataram, 2018)
This research is a development research (research and development) which aims to analyze the results of the development of the instrument of assessment of Basic Physics I practicum for students majoring in Physical Education UIN Alauddin Makassar theoretically and empirically in order to obtain a valid, reliable and feasible assessment. The development of assessment instruments refers to the design of test instrument development according to Kaharuddin Arafah which consists of 7 steps of development, namely: (1) Determining the measuring scale, measuring objectives and construction of measuring instruments, (2) Construction outcome measuring instruments, (3) Validation of contents, (4) Temporary measuring instruments, (5) Target of respondents for the trial, (6) Reliability, and (7) Measuring instruments ready for use. This research was tested in the Department of Physics Education Semester I 2016/2017 UIN Alauddin Makassar. The results of the study were obtained from the Basic Physics I practicum assessment instrument that produced 8 valid items, theoretically with reliability 1.0 and empirically reliability of 73.60%. The results of the study were obtained from the practicum assessment instrument that was declared valid and reliable and feasible to be used as a standard assessment instrument in the Department of Physics Education, UIN Alauddin Makassar.